The Digital Media Platforms and Students’ Emotional Intelligence during COVID-19 Pandemic in Malaysia - Abdul Aziz, Anis Atiqah; Nallaluthan, Kesavan; Kanapathy, Kaaminy; Kho, Fanny Chee Yuet; Zainal, Mazlan (Jurnal Pendidikan Bitara UPSI, 2022)
This study explored the relationship between social media and video games to the level of Malaysian secondary school students’ emotional intelligence during the COVID-19 pandemic. The self-administrated questionnaire was used for data collection and analyzed using Statistical Package for the Social Science (SPSS) software to get the mean, frequency, percentage, and correlation of Pearson. Results show that Cronbach’s Alpha reliability value for social media is 0.74, video games are 0.86 while the level of emotional intelligence is 0.80. Pearson correlation shows there is a relationship between social media with a level of emotional intelligence. Besides, the results of the study also show that there is no relationship between video games and the level of emotional intelligence. The findings of the study show that the mean for social media is 3.22, video games is 2.59 and the level of emotional intelligence is 3.30. The result of the descriptive analysis shows that the level of emotional intelligence of students is at a moderate level. Therefore, this study provides knowledge to individuals about the influence of digital media platforms that can provide an impact an individual’s level of emotional intelligence during the COVID-19 pandemic in Malaysia.